Experimental and Numerical Modeling of Magnetic Drug Targeting: Can We Trust Particle-Based Models? - Thalmayer, Angelika S.; Xiao, Keyu; Wolff, Paul; Fischer, Georg (IEEE journal on multiscale and multiphysics computational techniques, 2025)
The development of trustworthy simulation models is crucial for planning drug administration in magnetic drug targeting (MDT) interventions for future cancer treatment. In the MDT cancer therapy, the drug is bound to magnetic nanoparticles, which act as carriers and are guided through the cardiovascular system into the tumor region using an external magnetic field. Thus, the modeling represents a multiphysical problem and can be approached either by particle-based or concentration-based models. In this paper, both simulation approaches are implemented in COMSOL Multiphysics in a typical magnetic drug targeting scenario, verified by measurements, and compared among each other. Two different particle concentrations with and without an applied magnetic field of a Halbach array consisting of five permanent magnets in a tube flow system with a laminar velocity flow were investigated. Within this scope, an analytical model for calculating the system response for the detection of nanoparticles with a commercial susceptometer is derived, too. Considering the two implemented models and the investigated scenario, the concentration-based model shows a considerably better agreement with the experimental results for both with and without an applied magnetic field. The spatial resolution of the particle-based model is reduced due to the limited number of considered particles resulting in an inaccurate system response. Overall, the high number of new publications shows the need for research in this interdisciplinary research field to improve therapeutic success.